In-plane frictional resistances in dry block masonry walls and rocking-sliding failure modes revisited and experimentally validated. (1st January 2018) - Casapulla, C.; Argiento, L.U.
Abstract: This paper presents new findings in the assessment of the lateral strength of dry block masonry walls under in-plane loading, based on an existing macro-modelling approach using limit analysis methods. The evaluation of the in-plane frictional resistances activated at the onset of the rocking-sliding mechanisms is revisited and two equivalent formulations accounting for the self weight of the wall and additional loads are presented. The accuracy and robustness of the analytical results are assessed by experimentally testing both the resultant frictional resistances and their applications points. The solution procedure of the previous macro-block model providing upper and lower bounds for the ultimate load factor is also reconsidered and the computation of the "exact" load factor falling within the range is proposed. A satisfactory comparison is found with a micro-block and other macro-block models existing in the literature. This comparison is carried out through a parametric analysis, in terms of both the load factor and the failure mode and with reference to the effects of chosen parameters (wall aspect, unit aspect, unit size ratios and overload) on the load factor.